A study on the relationship between customer satisfaction and service level among ASNB agents at Seremban / Nurul Fazareen Roseli - Roseli, Nurul Fazareen (2009)
Satisfaction is an ambiguous and abstract concept and the actual expression of the situation of satisfaction will vary from person to person and service to service (R.Kantsperger and Werner,2005) . Beside, Customer satisfaction is affect organization differently, in different context of services. Studying customer satisfaction in different context of services will contribute to deeper understanding of the phenomenon as a whole and how to minimize its negative effect on satisfaction of customer. For instance, when customer experiencing bad services, this may override some of the negative effects on service quality of the organization. Hence, the purpose of the research is to describe customer satisfaction toward service level in the context of ASNB agents. Furthermore, the study is to examine the relationship of customer satisfaction and quality service level. Moreover, this research is conducted in order to measure the effectiveness of quality service level towards customer satisfaction at ASNB Seremban agents. A study is designed to identify whether the level of service counter, level of agents knowledge and service, level of ASNB unit trust Fund information and level of agents environment facilities is effective to satisfy the customers.